Control of Fusarium wilt disease by suppressing biofilms formation of Fusarium oxysporum f. sp. cubense using ginger essential oils nanofungicide - Abubakar, Abubakar Ismaila (2023)
Fusarium wilt is caused by Fusarium oxysporum f. sp. cubense (Foc) has been found to be a major banana disease that causes a devastating damages and huge yield loss because of biofilm development. In order to stimulate this effort, a series of experiments were conducted to examine the biofilm formation of Foc and susceptibility of Foc biofilms to environmental stress, profiling phytochemical compounds in ginger essential oils (EOs) and evaluate the antifungal activity of ginger EOs against Foc and develop, characterize and evaluate of formulated nanofungicides from ginger EOs. Findings of the research depicted that, Foc was able to produce abundant biofilms in the presence of glucose and sucrose. Comparatively, a lower quantity of biofilms was formed by the fungus in the manifestation of fructose and maltose. The biofilm formation of Foc was highest produced at 35°C followed by 25°C, 45°C and the lowest 15°C. The result of pH on the biofilm formation of Foc showed that pH 5 was highest to form biofilms followed by pH 9 and 7 while the lowest were pH 11 and 3. Phytochemical compounds present in the EOs were monoterpene and sesquiterpene hydrocarbons which differ in their composition and concentrations. In the suppression of Foc biofilms by EOs, food poisoned test (FPT) and cavity slide test (CST) were used to determine the percentage inhibition of fungal mycelia and conidia. Scanning electron microscope (SEM) micrographs of FPT revealed a significant antifungal effect against mycelia and conidia of Foc when treated with EOs at 5 μL/mL and 25 μL/mL compared with control. The effects were abnormal growth, lysis, shrinkage, disruption, and aggregation on both mycelia and spores. Similarly, transmission electron microscope (TEM) micrographs of the treated Foc conidia with EOs at 5 μL/mL and 25 μL/mL showed irreversible ultrastructural changes on the conidia. In the CST, SEM micrographs showed a significant antifungal effect on both mycelia and conidia of Foc treated with EOs at 5 μL/mL and 20 μL/mL compared with control. At 5 μL/mL level, the effects observed were abnormal growth, disruption, shrinkage and lysis on mycelia and conidia. Comparatively, at 20 μL/mL level, the antifungal effects detected were abnormal growth, lysis, shrinkage, disruption, and aggregation on both mycelia and spores of the fungus. Nanoemulsion of ginger EOs were prepared in which a ternary phase diagram (TPD) was constructed using a low-energy method based on non-ionic surfactant Tween 80, water, and EOs as the active ingredient. Findings of the glasshouse trial of the nanoformulations showed that treatment 250 μL/mL was the best based on suppression of disease severity index as well as AUDPC value when compared to the positive control. The results for the protection index (PI) showed that the TC4 (250 μL/mL) had the highest PI (20.38) and the lowest TC1 (100 μL/mL) with PI (15.46). In conclusion, the application of the prepared nanofungicide could effectively serve as a new antifungal agent in suppressing the growth of Fusarium wilt disease in-vivo trial and may also serve as an auspicious new alternative to synthetic fungicides.